Clinical/photographic evaluation of a single application of two sealants after eleven years - Sundfeld, Renato Herman [UNESP]; Mauro, Silvio José [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundfeld, Maria Lúcia Marçal Mazza [UNESP] (Tokyo Dental College, 2004)
The clinical behavior of Concise and Prisma Shield sealants for pit and fissure was analyzed by clinical/photographic evaluation. A hematoxylin-based staining solution was applied to the occlusal surface 7 days, 18 months, 36 months, and 11 years after the occlusal sealing, thus allowing the sealant material on the surface to be checked. At each analysis time, each occlusal surface was photographed, and the photographs corresponding to each time were submitted to clinical/photographic evaluation. Although the sealant materials showed marginal alterations over time, they did not require reapplication because the region composed of the pit and fissure remained covered.
Keywords: Pit and fissure sealants; Clinical/photograph study; Hematoxylin solution